AKSESIBILITAS PENDIDIKAN BAGI MAHASISWA DIFABEL DALAM RANGKA KESETARAAN HAK MEMPEROLEH PENDIDIKAN (STUDI DI UNIVERSITAS SEBELAS MARET SURAKARTA) - Pratiwi, Yuliani Dwi (PKn Progresif, 2015)
Considering the result of research, it could be concluded that: (1) education accessibility to disabled students in the attempt of obtaining appropriate solution in Surakarta Sebelas Maret University had been good although not all are disabled-friendly. So far, the disabled students existing in Surakarta Sebelas Maret University reported can access a variety of education supporting facility that had been provide by the campus. But there were some difficulties they found when they conducted education activity related to the distances between buildings existing in Surakarta Sebelas Maret University. (2) Some factors inhibited the education accessibility to the disabled students in the attempt of obtaining the equality of right to acquire education including (a) Regulation related to lift provision in lecturing building only for the four-storied or more building. (b) limited cost leading to many infrastructures or facilities were made friendly to the disabled. (c) Policy, there was no special rule or policy prepared for the disabled students including no special quota for disabled students admission, no special data about number or type of obstacles faced by the disabled students in Surakarta Sebelas Maret University. (d)  political will, there was some obstacles encountered in Surakarta Sebelas Maret University in providing education accessibility to the disabled students that are influenced by the political will are still lacking. (3) Solutions to overcome the obstacles in providing education accessibility to the disabled students in the attempt of obtaining the equality of right to acquire education included (1) to accelerate the construction of new disabled-friendly building, (2) to renovate the old building, (3) solution related to policy. The Surakarta Sebelas Maret University would take into account the student accessibility policy including special registration for disabled students in Surakarta Sebelas Maret University. (4). Solution related to political will. Increase officials political will in Surakarta Sebelas Maret University to overcome the obstacles in providing education accessibility to the disabled students in the attempt of obtaining the equality of right to acquire education.